English Lexical Collocation Error in Procedure Texts: A Case of Senior High School Students in Non-Formal Education - Arindi Indra; Sri Sarwanti; Gilang Fadhilia Arvianti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Developing a natural flow in English writing relies heavily on a learner's ability to pair words accurately through collocations. Unfortunately, students outside the formal schooling system rarely get enough targeted practice to master these specific lexical connections. The purpose of this study was to analyse the use of English lexical collocations in procedure texts written by senior high school students in non-formal education and to identify the factors associated with lexical collocation errors found in their writing. Employing a descriptive qualitative method, the data consisted of 15 student-written texts collected through a documentation technique. The data were analysed by identifying, classifying, and interpreting lexical collocations and collocation errors found in the texts. The results revealed that students still experienced difficulties in producing natural expressions, with 35 errors found across 89 identified collocations (an overall error rate of 39.33%). Specifically, Type L1(Verb + Noun) had the highest number of errors (48.57% with 17 errors), while Type L3(Adjective + Noun and Noun + Noun) showed the highest error rate within its own group (48.39%). These errors were mainly caused by limited vocabulary, literal translation, first language (L1) interference, limited collocational knowledge, and a lack of exposure to authentic English expressions. Nevertheless, several students successfully produced acceptable collocations such as mix well, stir well, boil the water, and add milk. The study concludes that explicit collocation instruction and greater exposure to authentic language are needed to improve students' procedural writing.